Critical Nationalism And Queer Decolonialities In The Philippine Classroom - Garcia, J. Neil C. (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
In this keynote for an online teacher training summit sponsored in 2022 by the Philippine Cultural Education Program of the National Commission for Culture and the Arts, the author reflects on the question of nationalism in relation to the challenge of mainstreaming the teaching of queer literature in our schools. In particular, he attends to the intersectionality between queerness and cultural and/or institutional nationalism, which he scrutinizes from the perspective of postcolonial and decolonial theories, as constitutively enlivened by the radically protean interests of anti-heteronormative politics. His reflection ranges from the saliency of deploying the idea of cultural translation in the way that we use anglophonic categories of gender and sexuality in our reading and analysis of classroom texts (a postcolonial task), to the decolonial recuperation of “egalitarian” and presexological ideas of gendered being and becoming, as urged upon us by a thoughtful consideration of our enduring oralities, the bulk of which remain eminently accessible to us through the mother-tongue reading (and teaching) of such extant folkloric “texts” as our archipelago’s plenitude of epics, myths, riddles, proverbs, and tales. All told, this keynote seeks to propose a specifically Philippine queer unpacking or deconstruction of the dominant form of nationalism that still holds sway in our educational system as a whole.